Radical Religious Expressions among Followers of Jamaah Anshorud Daulah (JAD) and Jamaah Ansharus Syariah (JAS) in Bima City: A Social Political Networks Perspective - Arief Hidayatullah; Syamsul Arifin; Tri Sulistyaningsih; Saiman (Internasional Journal of Politics and Public Policy, 2026)
This study examines radical religious expressions among Jamaah Anshorud Daulah (JAD) and Jamaah Anssar Syariah (JAS) in Bima City using a qualitative phenomenological approach grounded in George H. Mead's symbolic interactionism. Based on interviews with six members and twelve months of participant observation, the study finds contrasting patterns across key dimensions. JAD demonstrates rigid religious consciousness, subordinated identities, hierarchical interaction, organization-oriented action, and fixed symbolic meanings. In contrast, JAS shows more flexible religious understanding, greater individual agency, participatory social relations, transformative action, and adaptable symbols. These findings indicate that radical religious action is not spontaneous but develops through a gradual social process involving meaning interpretation, identity construction, group interaction, and symbolic deployment.